Study of Air Pollution CO2 in Surakarta City (Case Study at Adi Soemarmo Street, Slamet Riyadi Street and DR . Radjiman Street) - Asmara, Indria Tidar; , Drs. H. Yuli Priyana, M.Si; , Dra. Alif Noor Anna, M.Si (2016)
Research this was done in the city of Surakarta with the title : "Pollution Studies Air Carbon Dioxide (CO2) in the city of Surakarta (Case Study in the street of Adi Soemarmo, in the street of Slamet Riyadi and in the street of Dr. Radjiman). This research is based on a growing number of motor vehicles in the city of Surakarta, feared to raise the concentration of carbon dioxide (CO2) is continuously. The purpose of this research is : 1. To analyze the distribution of Carbon Dioxide (CO2) in the area of research, 2. To analyze the great of the relationship between the concentration of Carbon Dioxide (CO2) with air temperature, wind speed and the density of the motor vehicle in the area of research, 3. To compare the concentration of Carbon Dioxide (CO2) in the streets of the main road research area. The research method used in this research is a method of observation (survey) by doing measurement, observation, records and analysis. The data is collected and used in this research is the primary data obtained with the method of observation (survey) field. The source of secondary data obtained from publication Badan Pusat Statistik Kota Surakarta, Kantor Bersama Samsat and UP3AD Kota Surakarta, and Dinas Perhubungan Kota Surakarta. Data Analysis in graphics, statistics and descriptive. The results of the study showed that the distribution of the concentration of Carbon Dioxide (CO2) spatially in three main road city of Surakarta shows the tendency of the line that increased at a crossroads with the density of the motor vehicle high. The temperature correlation air and motor vehicle against Carbon Dioxide (CO2) 0,889 respectively, with the degree of trust 95% on the streets Slamet Riyadi in the night of the day. The value shows the very strong relationship and direction with significant value column (SIG) each 0,018. The speed correlation wind against Carbon Dioxide (CO2) -0,982, with the degree of trust 99% on the street of Adi Soemarmo at night. The value shows the very strong relationship, but inversely with significant value column (SIG) 0,003. The concentration Carbon Dioxide (CO2) highest from the three roads were in the streets Slamet Riyadi with the average amount of the concentration of Carbon Dioxide (CO2) on the morning of 604 ppm and on the night of 618 ppm. Key Words : air pollution, concentration, carbon dioxide